WhatsApp Application in English Language Teaching (ELT) Context: Media to Describe People - Syarifah Afsyah (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
Learning media is a vehicle and delivery of information or learning messages to students who can help teachers improve student achievement. Learning media always develops, along with technological developments. This study aims to analyze the function of learning media using WhatsApp in learning material describing people can support improving vocabulary in students that can be used in the learning process of teaching English in Senior High School. WhatsApp media can be used according to the level of student needs and material to be delivered. This type of research is a literature review by gathering sources of information and data from written documents in the form of articles, journals, and books. The conclusion of the study is the existence of the benefits of WhatsApp media that can be used by teachers for learning English in senior high school from simple material to complex material by utilizing technological developments and advancements.